2012
DOI: 10.4236/psych.2012.37075
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Informant Test Anxiety Assessment of Adolescents

Abstract: A total of 263 junior and senior high school students (grades 7, 8, 9, 10, 11, 12; ages 12 to 19) with relatively more informants identifying as females (57.4%) than males (42.6%) and more junior high school students (68.3%) than high school students (31.7%), along with 267 parents and 167 teachers responded to a student, parent, and teacher version of the German Test Anxiety Inventory (TAI-G) (Hoddapp & Benson, 1997). All reliabilities for all TAI-G scales for all three samples were above .70. The resulting d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 24 publications
3
13
1
3
Order By: Relevance
“…Sese et al (2010) reported deleting a poor fitting item on the 30-item TAI-G in order to obtain adequate structural validity in a Spanish sample, while in the Argentinian version, a total of two items were removed in order to obtain adequate fit (Heredia, Piemontesi, Burlan, & Hodapp, 2008). Furthermore, out of these studies, only two have examined the 17-item TAI-G (Harpell & Andrews, 2012;Hodapp & Benson, 1997), making support for the 17-item version limited. Moreover, the participants used in one study were Canadian students from Grades 7 to 12 (Harpell & Andrews, 2012), making generalisation to university populations questionable.…”
Section: Cultural Variants and The Tai-gmentioning
confidence: 96%
See 2 more Smart Citations
“…Sese et al (2010) reported deleting a poor fitting item on the 30-item TAI-G in order to obtain adequate structural validity in a Spanish sample, while in the Argentinian version, a total of two items were removed in order to obtain adequate fit (Heredia, Piemontesi, Burlan, & Hodapp, 2008). Furthermore, out of these studies, only two have examined the 17-item TAI-G (Harpell & Andrews, 2012;Hodapp & Benson, 1997), making support for the 17-item version limited. Moreover, the participants used in one study were Canadian students from Grades 7 to 12 (Harpell & Andrews, 2012), making generalisation to university populations questionable.…”
Section: Cultural Variants and The Tai-gmentioning
confidence: 96%
“…Furthermore, out of these studies, only two have examined the 17-item TAI-G (Harpell & Andrews, 2012;Hodapp & Benson, 1997), making support for the 17-item version limited. Moreover, the participants used in one study were Canadian students from Grades 7 to 12 (Harpell & Andrews, 2012), making generalisation to university populations questionable. In contrast, participants utilised by Hodapp and Benson (1997) comprised undergraduate university students from American and German samples.…”
Section: Cultural Variants and The Tai-gmentioning
confidence: 96%
See 1 more Smart Citation
“…Esto implica que la relación entre factores no puede ser omi da en el modelo analizado, ya que de ese modo se comete una mala especificación (Hu & Bentler, 1998) y podría perderse información importante que facilitaría una interpretación más certera de la estructura del TAI-E. Por otro lado, las elevadas correlaciones interfactoriales observadas tanto en estudios precedentes (Chapell et al, 2005;Oktedalen & Hagtvet, 2011;Papantoniou et al, 2011;Ware et al, 1990) como en los modelos oblicuos analizados en el presente estudio revelan que Emocionalidad y Preocupación no pueden ser considerados factores independientes, es decir, resulta di cil diferenciar ambos componentes en una situación de evaluación. Este parece ser una caracterís ca no solo del TAI, ya que otros instrumentos que enen como sustento el modelo dual también lo presentan (ver Ferrando, Varea, & Lorenzo, 1999) donde los componentes de Preocupación y Emocionalidad no se diferencian, o cuya correlación es de magnitud elevada (Harpell & Andrews, 2012;Heredia et al, 2008;Mowbray et al, 2015;Ringeisen et al, 2010); aunque también pudo influir otros factores, como el efecto piso, derivando en un factor de dificultad (Dominguez-Lara, 2013). Por ello, y con el respaldo del modelo bifactor analizado, un solo factor explica mejor la variabilidad de los ítems.…”
Section: Discussionunclassified
“…modificar algunos ítems) para minimizar el aparente solapamiento entre Preocupación y Emocionalidad (TAI-G; Hodapp, 1991). A pesar de ello, las correlaciones se man enen entre moderadas y altas (Harpell & Andrews, 2012;Heredia et al, 2008;Mowbray, Jacobs, & Boyle, 2015;Ringeisen, Buchwald, & Hodapp, 2010). Del mismo modo, el puntaje total fue jus ficado a través de modelos jerárquicos indirectos (e.g., Keith, Hodapp, Schermelleh-Engel, & Moosbrugger, 2003;Mowbray et al, 2015), aunque este no es el procedimiento más adecuado para evaluar la influencia directa del constructo de orden superior sobre los ítems (Canivez, 2016).…”
unclassified